The cisterna chyli and thoracic duct in pigs (Sus scrofa domestica) - M. Duras Gomercic; T. Trbojevic Vukicevic; T. Gomercic; A. Galov; T. Fruk; H. Gomercic (Veterinární Medicína, 2010)
Anatomical variations of the thoracic duct course are common in humans and domestic animals. They are important in thoracic surgery and in application of surgical techniques in experimental animals. The pig is a frequently used animal model due to numerous similarities between human and porcine anatomy and physiology. We revealed the position of the cisterna chyli, and the origin, course and termination of the thoracic duct by fine dissection on fifteen Yorkshire pig carcasses. The pigs were 2.5 months old with a body mass range from 10 to 15 kg. In this study we present our macroscopic observations. The cisterna chyli and thoracic duct had a common position, form and course in ten (67%) specimens. Anatomical variations of the precardiac course of the thoracic duct were observed in five animals (33%). Knowledge of these anatomical features should enhance the use of swine as an experimental model.